Diversity of rabies virus detected in Inner Mongolia, China, 2019–2021. Issue 2 (18th January 2022) - Feng, Ye; Wang, Yuyang; Hada; Deijide; Gaosuyilatu; Li, Xin; Xu, Zemin; Hasibagen; Bulage, Amur; Li, Linchuan; Sarula; Guo, Yu; et al.
Abstract: Rabies is a serious public health issue in China, with over 95% of human infections transmitted by dogs. As part of a routine surveillance carried out in the Inner Mongolia Autonomous Region (IMAR) between 2019 and 2021, 80 of 95 suspected rabies cases in domestic animals (dogs, livestock) and wild carnivores (foxes, badgers, a raccoon dog) were confirmed as rabies virus (RABV) positive. Phylogenetic analysis of RABVs of the 80 cases based on complete N genes showed that 97.5% (78/80) of the virus strains belonged to the Cosmopolitan (steppe‐type) clade, with one in each of Arctic‐related (AL2) and Asian (SEA1) clades. The data show that infected foxes have become a major transmission source of rabies in China, second only to dogs, and play a pivotal role in animal rabies epizootics in the north and northwest of the country. The recent spread of fox rabies to other animal species presents an increasing threat to public health and emphasizes the importance of animal rabies surveillance.